Probability of pharmacological target attainment with flucloxacillin in Staphylococcus aureus bloodstream infection: a prospective cohort study of unbound plasma and individual MICs. (8th April 2021) - Moser, Stephan; Rehm, Sophia; Guertler, Nicolas; Hinic, Vladimira; Dräger, Sarah; Bassetti, Stefano; Rentsch, Katharina M; Sendi, Parham; Osthoff, Michael
Abstract: Objectives: MSSA bloodstream infections (BSIs) are associated with considerable mortality. Data regarding therapeutic drug monitoring (TDM) and pharmacological target attainment of the β-lactam flucloxacillin are scarce. Patients and methods: We determined the achievement of pharmacokinetic/pharmacodynamic targets and its association with clinical outcome and potential toxicity in a prospective cohort of 50 patients with MSSA-BSI. Strain-specific MICs and unbound plasma flucloxacillin concentrations (at five different timepoints) were determined by broth microdilution and HPLC–MS, respectively. Results: In our study population, 48% were critically ill and the 30 day mortality rate was 16%. The median flucloxacillin MIC was 0.125 mg/L. The median unbound trough concentration was 1.7 (IQR 0.4–9.3), 1.9 (IQR 0.4–6.2) and 1.0 (IQR 0.6–3.4) mg/L on study day 1, 3 and 7, respectively. Optimal (100% fT >MIC ) and maximum (100% fT >4×MIC ) target attainment was achieved in 45 (90%) and 34 (68%) patients, respectively, throughout the study period. Conversely, when using the EUCAST epidemiological cut-off value instead of strain-specific MICs, target attainment was achieved in only 13 (26%) patients. The mean unbound flucloxacillin trough concentration per patient was associated with neurotoxicity (OR 1.12 per 1 mg/L increase, P  =   0.02) and significantly higher in deceased patients (median 14.8 versus 1.7 mg/L, P  =   0.01). Conclusions: Flucloxacillin pharmacological target attainment in MSSA-BSI patients is frequently achieved when unbound flucloxacillin concentrations and strain-specific MICs are considered. However, currently recommended dosing regimens may expose patients to excessive flucloxacillin concentrations, potentially resulting in drug-related organ damage.